PERBEDAAN ASUPAN MAKRONUTRIEN MAHASISWA ASING SEBELUM DAN SAAT TINGGAL DI SURABAYA, INDONESIA - Airin Levina; Lailatul Muniroh (PERSATUAN AHLI GIZI INDONESIA, 2018)
Population transfers between countries occur a lot, especially because of education. There are many international students in various parts of the world, including in Surabaya, Indonesia. Environmental differencescause changesin the eating habits that affect the amount of macronutrients intake among international students. The aims of this research was to analyze the differences of macronutrients intake among international students before and while live in Surabaya. This study was a cross-sectional design with 30 samples. Data were collected by in-depth interviews, the Dietary History instruments and Semi Quantitative Food Frequency Questionnaire through interview. Data were analized by t-test through the SPPS application. The results showed that there were differencesin macronutrient intake of international students before and during their stay in Surabaya (p0,005). There was a decrease in the average intake of energy, proteins, fat, and carbohydrates. It was due to inadequate access to food, often skipping meals, and can not accept the taste of Indonesian cuisine. Frequency and number of food portions of international students need to be increased.In addition, assistance from the universities are needed to increase access to food for international students.